Assessment choices to target higher order learning outcomes: the power of academic empowerment - Margot McNeill; Maree Gosper; Jing Xu (Association for Learning Technology, 2012)
Assessment of higher order learning outcomes such as critical thinking, problem solving and creativity has remained a challenge for universities. While newer technologies such as social networking tools have the potential to support these intended outcomes, academics’ assessment practice is slow to change. University mission statements and unit outlines may purport the value of higher order skills; however, questions remain about how well academics are equipped to design their curriculum and particularly their assessment strategies accordingly. This paper reports on an investigation of academic practice in assessing higher order learning in their units. Despite their intentions towards higher order learning outcomes for their students, the results suggest academics may make decisions when planning their assessment tasks that inadvertently lead students on the path towards lower order outcomes. Among the themes to emerge from the study is the importance of academics’ confidence and their attitudes towards the role of assessment in learning and how these perspectives, along with the types of learning outcomes they intend for their students, can influence their task design.